Exploring the Disease Pattern and Sociodemographic Profile among Patients Attending Patiya Upazila Health Complex of Chattogram (IAHS Medical Journal, 2025)
Background: To ensure satisfactory health care strategies of a country, morbidity and mortality data are very important. To understand the disease pattern and socio demographic profile of patients in rural Bangladesh.Materials and methods: This was a descriptive cross section study. Data were collected among patients coming to Patiya Health Complex from January 2024 to May 2024. Total 200 patients were interviewed through purposive sampling.Results: The study shows that 35(17.5%) belonged to age group 6 to 15 years, 50(25%) belonged to age group 16-30 years and 7(3.5%) were aged above 60 years. 136(68%) patients were female, 60(30%) were housewives, 110(55%) were married, 80(40%) had primary education and 120(60%) belonged to middle class. From the study it is also revealed that 110(55%) had a monthly income of Tk. 20,000 to 50,000 and 140(70%) belonged to joint family. Among the patients 120(60%) complained of fever, 112(56%) headache, 57(28.5%) loose motion, 78(39%) cough and 37(18.5%) skin rash. Study showed viral fever 150(75%), respiratory tract infections 49(24.5%), bronchial asthma 47(23.5%), 3(1.5%) dog bite, 8(4%) physical assault and 78(39%) skin diseases. Majority of the patients, 174(87%) said they were satisfied by the service rendered by the health complex.Conclusion: From the study, it is seen that the majority of diseases can be prevented.IAHS Medical Journal Vol 7(2), December 2024; 5-8